Emperor - Jones, Tommy Lee; Fox, Matthew; Momoi, Kaori; Hatsune, Eriko (Lionsgate, 2013)
Immediately after Emperor Hirohito's World War II surrender, General MacArthur suddenly finds himself the de facto ruler of a foreign nation. He challenges his expert on Japanese culture, General Fellers to provide evidence in ten short days to decide if the Japanese Emperor, worshipped as a god by his people but accused of war crimes, should be punished or saved, as the fate of a nation waits.